New Onset of Systolic Anterior Motion and Severe Mitral Regurgitation after Warm Ischemia in Donation after Circulatory Death Heart Transplantation - M Pozo Albiol; MJ Arguis; MJ Carretero; S Martínez Otero; P Caravaca; J Alcocer; R Navarro Ripoll (Annals of Cardiac Anaesthesia)
Donation after circulatory death is helping to expand the donor pool for heart transplantation. Nevertheless, these hearts are more susceptible to myocardial edema and decision of accepting the organ can be a challenge for the heart transplant team. Hemodynamic and echocardiographic criteria are used routinely, but there is still a lack of strong evidence that supports the decision-making in particular situations. That is why the authors found useful to analyze a case with a good outcome that could help accepting more organs in a situation of shortage.